2009
DOI: 10.4028/www.scientific.net/msf.610-613.293
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Catalytic Activity of Cu<sub>2</sub>O Films with Various Crystal Structures Prepared by DC Reactive Magnetron Sputtering

Abstract: The direct current (DC) reactive magnetron sputtering of a metal copper target in oxygen-argon mixed atmospheres to produce thin films of crystalline copper oxides was described. The sputtering pressure, sputtering power and oxygen flow rate were established in order to control the structures and properties of Cu2O films. The as-deposited Cu2O films with various crystal structures have high visible absorption and photo-catalytic activity under visible light irradiation. The photo-catalytic properties of Cu2O f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In fact, • OH and • OOH have not been isolated due to their ultrashort lifetime, but hydroxy intermediate compounds have been detected during the photodissociation . It has been reported that Cu 2 O absorbs visible light and cause the photodegradation of MB . The proposed mechanism for this reaction is based on the formation of a hydroxyl radical that results from the photodissociation of water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, • OH and • OOH have not been isolated due to their ultrashort lifetime, but hydroxy intermediate compounds have been detected during the photodissociation . It has been reported that Cu 2 O absorbs visible light and cause the photodegradation of MB . The proposed mechanism for this reaction is based on the formation of a hydroxyl radical that results from the photodissociation of water.…”
Section: Resultsmentioning
confidence: 99%
“…28 It has been reported that Cu 2 O absorbs visible light and cause the photodegradation of MB. 30 The proposed mechanism for this reaction is based on the formation of a hydroxyl radical that results from the photodissociation of water. Here we compare the efficiencies of Cu 2 O-Au nanoparticles of different thicknesses and having internal Au surfaces with pure Cu 2 O nanoparticles.…”
Section: Following Charge Separation On the Nanoscale In Cu 2 Oàau Na...mentioning
confidence: 99%
“…In our work, Cu 2 O was introduced as the template for the growth of Pt to enhance the properties of the bi-layers structure. As described above, the PtCl 25 This phenomenon, maybe due to these heterostructures, can lead to photoinduced charge separation more e±ciently. 26,27 In our work, the purpose of this research is to develop a facile and green route to synthesize Cu 2 OÀPt structure and study the role and mechanism toward the degradation of dye.…”
Section: Introductionmentioning
confidence: 88%